A Constitutive Relationship between Fatigue Limit and Microstructure in Nanostructured Bainitic Steels - Mueller, Inga (Materials (Basel), 2016)
The recently developed nanobainitic steels show high strength as well as high ductility. Although this combination seems to be promising for fatigue design, fatigue properties of nanostructured bainitic steels are often surprisingly low. To improve the fatigue behavior, an understanding of the correlation between the nanobainitic microstructure and the fatigue limit is fundamental. Therefore, our hypothesis to predict the fatigue limit was that the main function of the microstructure is not necessarily totally avoiding the initiation of a fatigue crack, but the microstructure has to increase the ability to decelerate or to stop a growing fatigue crack. Thus, the key to understanding the fatigue behavior of nanostructured bainite is to understand the role of the microstructural features that could act as barriers for growing fatigue cracks. To prove this hypothesis, we carried out fatigue tests, crack growth experiments, and correlated these results to the size of microstructural features gained from microstructural analysis by light optical microscope and EBSD-measurements. Finally, we were able to identify microstructural features that influence the fatigue crack growth and the fatigue limit of nanostructured bainitic steels.